Teacher’s Perceptions of Online Learning During COVID-19: A Study in SHS Indonesian Context - Siti Aisah Ginting (Asian TESOL Journal, 2022)
This study aims to investigate the English teachers' perception in Indonesia of online learning during COVID-19. This study applied a descriptive analysis approach, and the data were collected through interviews with English Teachers in Indonesia. The result shows that the English teachers’ perceptions toward online learning in the pandemic era are divided into three parts. First, they support facilitation like internet connection, gadgets, and quota. They were then followed by the learning process, such as the interaction, the explanation, the generation gap between teacher and students, the way to control students, and the challenges to create an effective climate towards the process.